2013
DOI: 10.4236/ape.2013.33019
|View full text |Cite
|
Sign up to set email alerts
|

Does Spine Posture Affect Isometric Torso Muscle Endurance Profiles in Adolescent Children?

Abstract: The purpose of this cross-sectional study was to examine mean values of isometric torso muscle profiles of four spinal postures (good posture, thoracic kyphosis, lumbar lordosis and scoliosis) among 743 children from the ages of 7 to 14 years old. It was hypothesized that having good posture, thoracic hyper-kyphosis, lumbar hyper-lordosis and scoliosis is linked to different isometric torso muscle endurance profiles. Torso muscle endurance, established through four tests (Biering-Sørensen Test for extensor end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
5
0
3
Order By: Relevance
“…We registered the laterally curved spine on 39,2%, the trunk inclination on 37,3%, the protruding abdomen on 35,3% and the hollow lower back on 46,1% of the cases. These fi ndings agree with other investigators, for example: the increased lumbar lordosis occurs on 32% of schoolchildren by Kratenova et al, [2], on 51,3% of male students by Asl and Savucu [9] and on 31%, on average, by Dejanovic et al, [4]. We could not confi rm the results of Kim et al (2006) [12] who found among adults that bigger imbalance between trunk extensors and fl exors is signifi cantly related to bigger lordotic curve which in turn can predict potential low back pain in the future.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We registered the laterally curved spine on 39,2%, the trunk inclination on 37,3%, the protruding abdomen on 35,3% and the hollow lower back on 46,1% of the cases. These fi ndings agree with other investigators, for example: the increased lumbar lordosis occurs on 32% of schoolchildren by Kratenova et al, [2], on 51,3% of male students by Asl and Savucu [9] and on 31%, on average, by Dejanovic et al, [4]. We could not confi rm the results of Kim et al (2006) [12] who found among adults that bigger imbalance between trunk extensors and fl exors is signifi cantly related to bigger lordotic curve which in turn can predict potential low back pain in the future.…”
Section: Resultssupporting
confidence: 93%
“…There are thoracolumbar extensors and iliopsoas together with rectus femoris in the shortened and tight muscle group, and abdominals together with gluteus medius and maximus on the weak group [5]. Poor posture is also related to a lower value in isokinetic strength of the trunk muscle [6] and also to a lower endurance capacity of trunk muscles, especially for hyper-lordotic spine [4]. But we cannot fi nd studies describing the ratios of muscle strength and grouping that assess the size of differences between the agonists and antagonists according to the impact on deviations in the posture.…”
Section: Already In 2004 Kopecky Brought Out: "The Main Reasonmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with erect posture, poor postures such as slumped sitting are associated with lower levels of spinal extensor muscle activation [63], which may result in damaging the oxygen transport capacity of muscles as well as pain and injury [68]. The relationship between posture and trunk muscle endurance and the relationship between sitting posture and back extensor muscle endurance have been researched in adolescents [72] and younger adults [71]. One study has been conducted investigating the endurance of the spinal extensor muscles in an elderly population with osteoporosis using EMG.…”
Section: Spinal Extensor Muscles and Age-related Hyperkyphosismentioning
confidence: 99%
“…Nustatyta, kad laikysena yra susijusi su liemens raumenų statinės ištvermės rodikliais (Dejanovic et al, 2013), o tie, kuriems nustatyta skoliozė, yra prastesnio funkcinio stabilumo (Nault et al, 2002). Visgi nedaug yra žinoma apie raumenų pakenkimus, raumenų funkcijas bei jų ryšius su laikysenos rodikliais esant IS (Parent, Richter, 2016).…”
Section: įVadasunclassified